2011
DOI: 10.1088/0953-8984/24/2/024205
|View full text |Cite
|
Sign up to set email alerts
|

Transverse and vortex domain wall structure in magnetic nanowires with uniaxial in-plane anisotropy

Abstract: Micromagnetic and analytical models are used to investigate how in-plane uniaxial anisotropy affects transverse and vortex domain walls in nanowires where shape anisotropy dominates. The effect of the uniaxial anisotropy can be interpreted as a modification of the effective wire dimensions. When the anisotropy axis is aligned with the wire axis (θ a = 0), the wall width is narrower than when no anisotropy is present. Conversely, the wall width increases when the anisotropy axis is perpendicular to the wire axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
3
17
0
1
Order By: Relevance
“…8(b)), the area of a domain around the pad's center increased and invaded into the wire. As a result, a vortex type DW 38) where the local moment formed a closed loop was injected as indicated by the arrowhead. Note that the edge contrast of the wire alternated between the left and right parts of the wire.…”
Section: Domain Wall Injection and Movement In A Py Wirementioning
confidence: 99%
“…8(b)), the area of a domain around the pad's center increased and invaded into the wire. As a result, a vortex type DW 38) where the local moment formed a closed loop was injected as indicated by the arrowhead. Note that the edge contrast of the wire alternated between the left and right parts of the wire.…”
Section: Domain Wall Injection and Movement In A Py Wirementioning
confidence: 99%
“…It has recently been shown that the addition of a uniaxial anisotropy contribution in permalloy nanowires can either increase or decrease the domain wall width [13]. Walker breakdown effects can also be suppressed and a 30% increase in domain wall velocity was reported in a similar system when the in-plane anisotropy was oriented perpendicular to the wire long axis [14].…”
Section: Domain Wall Widthmentioning
confidence: 99%
“…In effect, this removes the demagnetizing field from the ends of the wire. Given that the magnetization profile differs substantially with the addition of a uniaxial anisotropy, and differs significantly from a transverse to vortex structure, we define the domain wall width to be the region enclosed by M x /M s = ±0.95, thus allowing a direct comparison of domain wall widths, which is independent of wall structure [13]. Without a uniaxial anisotropy, the width of a transverse domain wall, ΔTW, was measured to be 125 nm, and the width of a vortex domain wall, ΔVW, was measured to be 258 nm in a LSMO nanowire.…”
Section: Domain Wall Widthmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the vortex dynamics has received a growing interest, since it can be described as a rigid magnetic configuration by a single parameter. 4 It is important in nanowires, being energetically more stable than the transverse wall for large wire cross-sections (vortex wall), 5 as well as in disks. In vortex domain walls, core switches can occur at material defects, 6 while in nano-disks the magnetic vortex configuration was employed to probe single defects.…”
mentioning
confidence: 99%